2006
DOI: 10.1016/j.yjmcc.2006.03.433
|View full text |Cite
|
Sign up to set email alerts
|

Differential hypertrophic effects of cardiotrophin-1 on adult cardiomyocytes from normotensive and spontaneously hypertensive rats

Abstract: Cardiotrophin-1 (CT-1) produces longitudinal elongation of neonatal cardiomyocytes, but its effects in adult cardiomyocytes are not known. Recent observations indicate that CT-1 may be involved in pressure overload left ventricular hypertrophy (LVH). We investigated whether the hypertrophic effects of CT-1 are different in cardiomyocytes isolated from adult normotensive and spontaneously hypertensive rats (SHR). Hypertrophy was evaluated by planimetry and confocal microscopy, contractile proteins were quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
4
39
0
Order By: Relevance
“…A previous study demonstrated that LIFR plays a critical role in the cardiotrophin-1-induced longitudinal prolongation of cardiomyocytes during heart development (17). We verified the upregulation of LIFR, and the Western blot in Fig.…”
Section: Rod-shaped Morphology and Striation Pattern Were Preserved Isupporting
confidence: 79%
See 1 more Smart Citation
“…A previous study demonstrated that LIFR plays a critical role in the cardiotrophin-1-induced longitudinal prolongation of cardiomyocytes during heart development (17). We verified the upregulation of LIFR, and the Western blot in Fig.…”
Section: Rod-shaped Morphology and Striation Pattern Were Preserved Isupporting
confidence: 79%
“…The increased expression of LIFR in 2-mo-old cTnI-K118C mouse ventricular muscle linked the cTnI-K118C mutation to a cell signaling pathway that has been demonstrated to have an essential role in longitudinal prolongation of rat cardiomyocytes via the function of the cardiotrophin-1 signaling pathway (17,29). The signals may originate from the altered contractility or through changes in Ca 2ϩ homeostasis due to altered troponin function.…”
Section: Discussionmentioning
confidence: 99%
“…Despite years of intensive research, the exact mechanisms mediating CT-1-induced cardiomyocyte hypertrophy are still not entirely clarified. Originally, activation of the JAK/STAT3 axis has been assigned the key role in the generation of a cardiac hypertrophic phenotype in response to CT-1 stimulation [88,116,127,140]. While it appears quite certain that CT-1-induced cardiac hypertrophy is independent of PI3-K/Akt signaling [140], recent findings indicate that the major pathway responsible for the hypertrophic responses to CT-1 is probably not the JAK/STAT3 pathway or the MEK1-ERK1/2 pathway, but signal transduction via the MEK5-ERK5 pathway [134].…”
Section: Cardiotrophin-1 and Its Potential Role In The Heartmentioning
confidence: 99%
“…A large number of experimental studies demonstrate that CT-1 may induce myocardial hypertrophy 1,7 . It also has been shown that the expression of CT-1 in the post-MI heart issignificantly elevated 8 .…”
Section: Disscusionmentioning
confidence: 99%